(untitled) (American Journal of Islam and Society, 2017)
Books Reviewed:Azra Akšamija, Mosque Manifesto: Propositions for Spaces of Coexistence. Berlin: Revolver Publishers, 2015; Christiane Gruber, ed., Islamic Architecture on the Move: Motion and Modernity. Bristol: Intellect, 2016; Bernard O’Kane, The Mosques of Egypt. Cairo: American University in Cairo Press, 2016. It may seem to some people that writing about the architecture of Islam and the mosque, the Islamic building par excellence, is an exercise in reiterating the past and earlier finds – possibly packaging what is already known in an attractive visual format. What these three books have in common is the effort to analyze these two subjects in a new way and in line with three very different methods. Azra Akšamija’s Mosque Manifesto: Propositions for Spaces of Coexistence is a collection of ten of her original research-creation pieces framed by ten articles. Research-creation is a hybrid scholarly approach that “supports the development of knowledge and innovation through artistic expression, scholarly investigation, and experimentation.”1Although she does not use this term, one should keep it in mind while reviewing the context and impact of her artistic work. Trained as an architect, she is also a historian and practicing artist, a designer and professor. Her productions critically review and express her proposed ten points of design. This vantage point is clearly unique, in that the material is primary and generative. Christiane Gruber’s edited Islamic Architecture on the Move: Motion and Modernity compiles the voices of eight academics reflecting on specific aspects of the physical and ideological movement of Islamic ideas and forms. Some of the contributions rely heavily on previous research; however, three essays are original research. In The Mosques of Egypt, O’Kane showcases his photographs of over eighty mosques. His academic expertise and experience in editing the works of renowned Islamic scholars gives him a unique position, and his excellent book includes both contemporary and detailed documentation of well-studied buildings, several lesser known structures, and several modern mosques. Tellingly, each book’s structure betrays a great deal about how its content is to be received, for those who practice and study the arts are well aware of an object’s power of visual and tactile qualities, even if that object happens to ...